Ability Test of Acacia Nilotica Leaves and Extract As Water Disinfectants - Miftahul El Jannah, Syarifah; Prabowo, Kuat; Kriswandana, Ferry (KnE Life Sciences, 2019)
The fulfillment of clean water that meets bacteriological requirements for urban areas is increasingly difficult due to the high contamination of groundwater by microbes. The use of chemical compounds as disinfectants always produces long-term side effects, it is necessary to develop plants that can be used as disinfectants. Acacia nilotica has the ability to kill aerobic and coliform bacteria so that it has the potential to disinfect water. The study aimed to examine the ability of leaves and extracts of A. nilotica leaves that grow in the Baluran National Park in East Java in reducing the number of aerobic and coliform bacteria in clean water used by the community. Water samples were taken from the residents of Rt 006/011 Kebayoran lama with bacteriological quality criteria Total Plate Number (TPC) above 4.0 x 10 [2]CFU and MPN Coliform> 2400 cells/100ml. The leaves of A. nilotica are used at concentrations of 30%, 40%, and 50%, and ethanol extract of leaves of A. nilotica 5%, 7.5%, and 10% after 1 hour, 3 hours, 6 hours and 24 hours of contact. A coliform examination was performed on TPC and MPN. The yield of A. nilotica leaves was effective in reducing aerobic bacteria to 99.6% at a concentration of 50% after 24-hour contact, while leaf extract reduced the number of aerobic germs to 99.7% at a concentration of 10%. While MPN Coliform is reduced to 99.5% in the application of 50% of leaves of A. nilotica, the extract of A. nilotica can reduce coliform MPN to 100% at a concentration of 10%.